Rewrite as a simplified fraction.
2.37 = ?
[tex]\frac{237}{100}[/tex]
Step-by-step explanation:Hi there !
2.37 = 237/100
Good luck !
Find the length of a line segment with endpoints of –9 and 7.
A.
–16
B.
–2
C.
16
D.
26
Please select the best answer from the choices provided
A
B
C
D
Answer:
c 16
Step-by-step explanation:
HURRY ILL MARK BRAINLIEST
Answer: B & D
Step-by-step explanation: Trust me
What is the value of x in the equation x^ 3 = 8 /216
Answer:
x=1/3
Step-by-step explanation:
Answer:
1/3
Step-by-step explanation:
8/126 = 1/27. 1/27 is a cube because 1/3 can be multiplied by itself three times to get it.
i need help on this one too
Answer:
x equals 3
Step-by-step explanation:
hope this helps
i need help with my math
Answer:
a - 8^2
b-2^8
c-4^2
d-2^4
Answer:
The first on the left is the last one on the right, the second on the left is the second on the right, the third on the left is the third on the right, and the fourth on the left is the first on the right. Hope this helps.
Step-by-step explanation:
6. Describe and correct the error in solving the equation.
X Х
0.4x = 0.2(x.-8)
0.4x = 0.2 x - 8
0.2x = -8
x = -4.
What is the area of this tile?
3 in.
3 in.
Answer:
9 in. i think
Step-by-step explanation:
Evaluate the expression for the given values of the variables.
5d − 4e − 14 for d = 5 and e = −7
When d = 5 and e = −7, the expression is equal to
Answer:
39
Step-by-step explanation:
5(5) - 4(-7) - 14 is what the equation should look like.
Just simplify the expression.
Is π 100 rational or irrational
Answer:
it is irrational
Step-by-step explanation:
hope this helps
plz give brainliest
Answer:
Pi is an irrational number.
Step-by-step explanation:
It's a never ending number.
How would you simplify 3, 999, 999^0
Answer:
4,000,000^0 your welcone
Algebra II Question One 4-2 HW
Answer:
mark crumbs inm om fro i.v om
A = 243
B = 1/10 or 0.1
The time, in seconds, that it takes a pendulum to swing back and forth is modeled by the equation below. f (l) = 2 pi StartRoot StartFraction l Over 32 EndFraction EndRoot, where l is the length of the pendulum in feet What is the approximate length of a pendulum that takes 2.4 pi seconds to swing back and forth?
Answer:
46.08 feet.
Step-by-step explanation:
Given that, for length, [tex]l[/tex] feet, the time period, [tex]f(l)[/tex], of the pendulum is
[tex]f(l)=2\pi\sqrt{\frac{l}{32}}[/tex].
As the time period equals the time taken by the pendulum in one back and forth motion, so, actually, the given [tex]2.4\pi[/tex] seconds to swing back and forth is the time period.
Let [tex]l_0[/tex] feet be the length of the pendulum for the time period [tex]2.4\pi[/tex] seconds, so
[tex]f(l_0)=2.4\pi[/tex]
[tex]\Rightarrow 2\pi\sqrt{\frac{l_0}{32}}=2.4\pi[/tex]
[tex]\Rightarrow \sqrt{\frac{l_)}{32}}=1.2[/tex]
[tex]\Rightarrow \frac{l_0}{32}=(1.2)^2[/tex] [squaring on both the sides]
[tex]\Rightarrow l_0=1.44\times32[/tex]
[tex]\Rightarrow l_0=46.08[/tex]
Hence, the approximate length of a pendulum that takes [tex]2.4 \pi[/tex] seconds to swing back and forth is 46.08 feet.
Answer:
the answer is d on edge 2020
Step-by-step explanation:
The red dot is located between 12 and 13. The red dot is about half way between 12 and 13, but a little below the half way point, so the red dot represents a little below half way between the two square roots. Since the square root of 144 is equal to 12 and the square root of 169 is equal to 13, then the red dot is located between the two square roots. By extension, to the nearest integer, the approximate value of the dot will be a little below half way between and , which is about the square root of .
Answer:
The answer is "156".
Step-by-step explanation:
According to the question, the 144 square root equals 12. The 169 square root equals 13, and by extending the estimated price of blackness, only at the nearest entry, has been a little or less halfway between both the 144 square root and the 169 square root estimated, at 156 square root, that's why 156 is the correct answer.
A number line graph is shown:
-8 -7 -6 -5 -4 -3 -2 -1 0 1 2 3 4 5 6 7 8
Based on the graph, which inequality is correct for a number that is to the right of -4?
0-2 <-4
O-3>-4
0 1 <-4
-5 >-4
Answer:
1<-4
Step-by-step explanation:
Answer:
-3 > -4 i believe i hope this helps!!
Step-by-step explanation:
Write the equation of a quadratic with x-intercepts at (-1,0) and (4,0)
Answer:
y = x² - 3x - 4
Step-by-step explanation:
Given that the x- intercepts are x = - 1 and x = 4, then the corresponding factors are
(x + 1) and (x - 4) and the quadratic is the product of the factors, that is
y = (x + 1)(x - 4) ← expand using FOIL
y = x² - 3x - 4
Select the correct answers.
A pair of parallel lines is cut by another pair of parallel lines as shown in the figure. Which angles are congruent to angle K?
R
D
N
А
P
E
M
H
F
G
K
O A angles P, Q, and R
OB. angles M, E, and
OC angles G, A, and B
OD. angles D, E, and
E angles M, N, and P
Answer:it is c
Step-by-step explanation:
Answer:b
Step-by-step explanation:
WILL GIBE BRAINLIEST
Use FOIL to determine the following Expression
Answer:
0=0, Infinite solutions
Step-by-step explanation:
For an answer to have an infinite solution, the two equations when you solve will equal 0=0. Here is a problem that has an infinite number of solutions. If you solve this your answer would be 0=0 this means the problem has an infinite number of solutions.
If this was helpful please give brainliest, have a great day!
x=2
x=10
Woulld really appriciate brainliest here is the steps below
1.1 Factoring x2-12x+20
The first term is, x2 its coefficient is 1 .
The middle term is, -12x its coefficient is -12 .
The last term, "the constant", is +20
Step-1 : Multiply the coefficient of the first term by the constant 1 • 20 = 20
Step-2 : Find two factors of 20 whose sum equals the coefficient of the middle term, which is -12 .
-20 + -1 = -21
-10 + -2 = -12 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -10 and -2
x2 - 10x - 2x - 20
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-10)
Add up the last 2 terms, pulling out common factors :
2 • (x-10)
Step-5 : Add up the four terms of step 4 :
(x-2) • (x-10)
Which is the desired factorization
Equation at the end of step
1
:
(x - 2) • (x - 10) = 0
STEP
2
:
Theory - Roots of a product
2.1 A product of several terms equals zero.
When a product of two or more terms equals zero, then at least one of the terms must be zero.
We shall now solve each term = 0 separately
In other words, we are going to solve as many equations as there are terms in the product
Any solution of term = 0 solves product = 0 as well.
Solving a Single Variable Equation:
2.2 Solve : x-2 = 0
Add 2 to both sides of the equation :
x = 2
Solving a Single Variable Equation:
2.3 Solve : x-10 = 0
Add 10 to both sides of the equation :
x = 10
Supplement : Solving Quadratic Equation Directly
Solving x2-12x+20 = 0 directly
Earlier we factored this polynomial by splitting the middle term. let us now solve the equation by Completing The Square and by using the Quadratic Formula
Parabola, Finding the Vertex:
3.1 Find the Vertex of y = x2-12x+20
Parabolas have a highest or a lowest point called the Vertex . Our parabola opens up and accordingly has a lowest point (AKA absolute minimum) . We know this even before plotting "y" because the coefficient of the first term, 1 , is positive (greater than zero).
Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two x -intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.
Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to be able to find the coordinates of the vertex.
For any parabola,Ax2+Bx+C,the x -coordinate of the vertex is given by -B/(2A) . In our case the x coordinate is 6.0000
Plugging into the parabola formula 6.0000 for x we can calculate the y -coordinate :
y = 1.0 * 6.00 * 6.00 - 12.0 * 6.00 + 20.0
or y = -16.000
Parabola, Graphing Vertex and X-Intercepts :
Root plot for : y = x2-12x+20
Axis of Symmetry (dashed) {x}={ 6.00}
Vertex at {x,y} = { 6.00,-16.00}
x -Intercepts (Roots) :
Root 1 at {x,y} = { 2.00, 0.00}
Root 2 at {x,y} = {10.00, 0.00}
Solve Quadratic Equation by Completing The Square
3.2 Solving x2-12x+20 = 0 by Completing The Square .
Subtract 20 from both side of the equation :
x2-12x = -20
Now the clever bit: Take the coefficient of x , which is 12 , divide by two, giving 6 , and finally square it giving 36
Add 36 to both sides of the equation :
On the right hand side we have :
-20 + 36 or, (-20/1)+(36/1)
The common denominator of the two fractions is 1 Adding (-20/1)+(36/1) gives 16/1
So adding to both sides we finally get :
x2-12x+36 = 16
Adding 36 has completed the left hand side into a perfect square :
x2-12x+36 =
(x-6) • (x-6) =
(x-6)2
Things which are equal to the same thing are also equal to one another. Since
x2-12x+36 = 16 and
x2-12x+36 = (x-6)2
then, according to the law of transitivity,
(x-6)2 = 16
We'll refer to this Equation as Eq. #3.2.1
The Square Root Principle says that When two things are equal, their square roots are equal.
Note that the square root of
(x-6)2 is
(x-6)2/2 =
(x-6)1 =
x-6
Now, applying the Square Root Principle to Eq. #3.2.1 we get:
x-6 = √ 16
Add 6 to both sides to obtain:
x = 6 + √ 16
Accordingly, B2 - 4AC =
144 - 80 =
64
Applying the quadratic formula :
12 ± √ 64
x = —————
2
Can √ 64 be simplified ?
Yes! The prime factorization of 64 is
2•2•2•2•2•2
To be able to remove something from under the radical, there have to be 2 instances of it (because we are taking a square i.e. second root).
√ 64 = √ 2•2•2•2•2•2 =2•2•2•√ 1 =
± 8 • √ 1 =
± 8
So now we are looking at:
x = ( 12 ± 8) / 2
Two real solutions:
x =(12+√64)/2=6+4= 10.000
or:
x =(12-√64)/2=6-4= 2.000
x=10
x=2
Hope this helps Would also appriciate brainliest
please help!!!!! thank you!!! any help would be appreciated!!
Answer:
I would say c. you welcome for my so called help
To determine the number of deer in a forest, a forest ranger tags 280 and releases them back into the forest. Later, 405 deer are caught, out of which 45 of them are tagged. About how many deer are in the forest?
Answer:
640
Step-by-step explanation:
405-45= 360
360+280=640
Answer:
2520 deerStep-by-step explanation:
Given
Tagged deer = 280Caught deer = 405Tagged among caught = 45The ratio of the tagged deer vs total
45 ⇔ 405280 ⇔ xSolving by cross-multiplication
45x = 405*280x = 405*280/45x = 2520So there are about 2520 deer in the forest
Please help me.
In a group of 45 students at a school, all students must study at least one science. Physics is compulsory, but students may also opt to study chemistry or biology or both. 9 students take all three sciences. 24 take both physics and biology (with or without chemistry). 12 students take only physics. How many are studying chemistry and physics but not biology?
Answer:
9 students
Step-by-step explanation:
Let x be the number of students taking only Physics and Chemistry
Number of students :
All 3 sciences = 9
Only physics = 12
Both Physics and Biology( without Chem ) = 24 -9 = 15
15+ 9 + 12+x = 45 , since Physics is compulsory
36 + x = 45
x = 45 - 36
x = 9
Hope it helps :)
Answer:
9
Step-by-step explanation:
First to answer gets something good ;)
Answer:
should be the second one 75 + 20x <55 +44x
PLEASE HELP! I left to go eat and when I came back I forgot what I was doing.
The image shown is of two sets of parallel lines.
The m∠ 13 = 29x - 2 and the m∠ 9 = 27x + 6
What is the m∠ 12?
Answer:
x=4
m<12 = 66
Step-by-step explanation:
Answer:
x = 4
m∠12 = 66
m∠13 and m∠12 are linear pairs (supplementry angles)
Step-by-step explanation:
m∠9 ≈ m∠15 (Vertical angle)
m∠15 ≈ m∠13 (Corresponding angle)
m∠9 ≈ m∠13
29x - 2 = 27x + 6
2x - 2 = 6
2x = 8
x = 4
m∠13 = 29(4) - 2
m∠13 = 114
m∠13 + m∠12 = 180
180 - m∠13 = m∠12
180 - 114 = 66
m∠12 = 66
Question 4 Multiple Choice Worth 1 points)
(04.02 LC)
What is the solution to the following system of equations?
X - 3y = 5
2x + y = 10
(5,0)
(0,5)
(7,0)
(0,7)
Answer:
What do you mean?
Step-by-step explanation:
Answer:
( 5, 0 )Step-by-step explanation:
x - 3y = 5
2x + y = 10 multiply by 3 to eliminate y and solve for x
x - 3y = 5
6x + 3y = 30 then add
7x = 35
simplify:
x = 35 / 7
x = 5
substitute x = 5 back into the eq.2
2x + y = 10
2(5) + y = 10
y = 10 - 10
y = 0
therefore the answer is ( 5, 0 )
write 1.359 x 10^5 in standard form
The given number is already in the standard form i.e. 1.359 x 10⁵.
What is standard form?Standard form refers to any number that may be expressed as a decimal number between 1.0 and 10.0 when multiplied by a power of 10.
When working with extremely big or extremely small numbers, standard form, also known as standard index form, may be quite helpful. It is based on the use of powers of 10 to describe the size of a number.
Scientists may compare the orders of magnitude of various values using standard form, which enables them to understand events and make helpful predictions.
It is given that,
1.359 x 10⁵
We have to convert the given number is in standard form.
Thus, the given number is already in the standard form i.e. 1.359 x 10⁵.
Learn more about the standard form here,
https://brainly.com/question/17264364
#SPJ2
Rachel and her cousin, Lena, live in different cities that are about 100 miles apart. On a map, the two cities measure
5 inches apart. What is the scale factor used for the map?
Answer:
Step-by-step explanation:
On her map 1 inch is equal to 20 miles.
5x=100
divide both sides by 5
x=20
Substitute the length of the sides (7 in, 25in n)
into the Pythagorean theorem. Then, find the length of the missing side m
(Please with step by step answer)
Answer:
with 2 sides, we can assume that the 25 inch side is the hypotenuse.
7^2 + 25^2 = 49 + 625 = 674
674 is NOT a perfect square so we'll make the 25 side as the hypotenuse.
7^2 +n^2 = 625
n^2 = 625 - 49
n^2 = 576
square root (576) = 24
So the 3 sides are
7 24 and 25
Step-by-step explanation:
28+7+2=x+1
Solve equation
Answer:
x= 36
Step-by-step explanation:
28+7+2= 37
37= x+1
37-1= 36
x= 36
Answer:
x = 36
Step-by-step explanation:
28 + 7 + 2 = x + 1
x + 1 = 28 + 7 + 2
x + 1 = 37
x = 37 - 1
x = 36
I hope this helped!
what's
[tex]4 \times4 \times 4[/tex]
what's 4 * 4
Answer:
4×4×4 = 64
4×4 = 16
Explanation : 4×4×4 could also be 4 to the third power .
Answer: The answer to this basic math question with the 2 given following basic math expressions are the following answers that have been provided to you:
[tex]4 * 4 * 4 = 64.[/tex] [tex]4 * 4 = 16.[/tex]Step-by-step explanation: Mmmm, that was super extremely easy, so anyway, here is a basic step in order to evaluate the 2 given following basic math expressions:
[tex]4 * 4 * 4[/tex] could also be 4 to the third power. [tex]4 * 4[/tex] could also be 4 to the second power.It means it's the exponent power.
I hope that my full given answer with my full given step-by-step explanation is very helpful to your own basic math question with the 2 given following basic math expressions, please mark me as Brainliest, take care, always be safe, and have a great holiday winter break, Merry Christmas and a happy new year! :D
Sincerely,
Jason Ta,
The Ambitious of The Brainly And The Role of The TDSB And WHCI Student of The High School.
If anyone can help me please with the this problem (picture above)
Answer:
6x-3=9
Step-by-step explanation:
i dont really get what it means by set up an equation but heres what i know-
36 is the perimeter so divide it by 4 to get the length of each side-
36/4=9
now you know that each side is 9, so 6x-3=9
when you solve that, x=2